Treatment-associated mRNA co-expression changes in monocytes of patients with posttraumatic stress disorder - Kumsta, Robert; Zang, Johannes C. S.; Hummel, Elisabeth M.; Müller, Svenja; Moser, Dirk A.; Herpertz, Stephan; Kessler, Henrik (Frontiers in Psychiatry, 2023)
PTSD is a prevalent mental disorder that results from exposure to extreme and stressful life events and comes at high costs for both the individual and society. Therapeutic treatment presents the best way to deal with PTSD - the mechanisms underlying change after treatment, however, remain poorly understood. While stress and immune associated gene expression changes have been associated with PTSD development, studies investigating treatment effects at the molecular level so far tended to focus on DNA methylation. Here we use gene-network analysis on whole-transcriptome RNA-Seq data isolated from CD14+ monocytes of female PTSD patients (N = 51) to study pre-treatment signatures of therapy response and therapy-related changes at the level of gene expression. Patients who exhibited significant symptom improvement after therapy showed higher baseline expression in two modules involved in inflammatory processes (including notable examples IL1R2 and FKBP5) and blood coagulation. After therapy, expression of an inflammatory module was increased, and expression of a wound healing module was decreased. This supports findings reporting an association between PTSD and dysregulations of the inflammatory and the hemostatic system and mark both as potentially treatment sensitive.